CHARACTERIZATION OF BEVERAGE QUALITY IN Coffea canephora Pierre ex A. Froehner - Souza, Carolina Augusto de; Rocha, Rodrigo Barros; Alves, Enrique Anastácio; Teixeira, Alexsandro Lara; Dalazen, Janderson Rodrigues; Fonseca, Aymbiré Francisco Almeida da (Coffee Science - ISSN 1984-3909, 2018)
Differentiation of coffee according to its quality can result in added value. Both the coffee genotype and the environment influence beverage quality. The main species grown in the Amazon region is C. canephora, which includes two distinct botanical varieties: Conilon and Robusta. The aim of this study was to characterize beverage quality in C. canephora and distinguish the Conilon and Robusta botanical varieties and intervarietal hybrids. We evaluated the beverage quality of 130 superior clones from samples of hulled coffee collected in the experimental field of Embrapa Rondônia in the municipality of Ouro Preto do Oeste, RO, Brazil. The beverage was classified according to the Robusta Cupping Protocols, which also considers the nuances of the beverage, described as neutral, fruit-like, exotic, refined, and mild. The final mean values classified the Robusta botanical variety and the intervarietal hybrids as coffees with a premium beverage, and the Conilon botanical variety as usual good quality. The nuances of the Conilon botanical variety were found to be predominantly neutral (78%), as compared to the Robusta botanical variety and the intervarietal hybrids, which exhibited 50% and 44% of their beverages, respectively, with fruit-like, exotic, or mild nuances. The genetic parameters indicate that the genetic component was more important than the environmental in expression of coffee quality attributes. Genetic variability was observed in the population evaluated, except for the Uniform Cup and Clean Cup beverage attributes.